2020
DOI: 10.1038/s41598-020-65758-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Echocardiography-Derived Left Ventricular Stiffness Index in Low-Flow Versus Normal-Flow Severe Aortic Stenosis with Preserved Left Ventricular Ejection Fraction

Abstract: Background Paradoxical low-flow (LF) severe aortic stenosis (AS) with preserved left ventricular ejection fraction (LVEF) may have poorer prognosis than normal-flow (NF) AS, though its pathophysiology remained unclear. In particular, LV stiffness has not been compared between LF vs NF. We used a novel echocardiography-derived index of LV stiffness to compare between these groups. Consecutive patients with medically-managed isolated severe AS (aortic valve area < 1 cm 2) and preserved LVEF (>50%) were studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…We found that EDV and SVI had –ve correlation with LV stiffness index and + ve correlation with DWS, in agreement with Ngiam et al [ 26 ] who stated that the higher the LV stiffness, the lower EDV and SVI. On multivariable analysis we found that AF was only associated with reduced DWS and increased LV stiffness index, which are contributing factors in subtle diastolic dysfunction, patients with reduced DWS (< 0.33) and high LV stiffness index (> 0.13 ml −1 ) had a higher risk to develop AF.…”
Section: Discussionsupporting
confidence: 92%
“…We found that EDV and SVI had –ve correlation with LV stiffness index and + ve correlation with DWS, in agreement with Ngiam et al [ 26 ] who stated that the higher the LV stiffness, the lower EDV and SVI. On multivariable analysis we found that AF was only associated with reduced DWS and increased LV stiffness index, which are contributing factors in subtle diastolic dysfunction, patients with reduced DWS (< 0.33) and high LV stiffness index (> 0.13 ml −1 ) had a higher risk to develop AF.…”
Section: Discussionsupporting
confidence: 92%
“…The tangent slope of any point on this curve (dP/dV) is called the left ventricular lumen stiffness. And K is the slope of the linear relationship between ventricular stiffness and ventricular pressure, reflecting left ventricular Passive diastolic function [ 17 , 18 ]. Coronary pressure was measured by end-diastolic coronary volume (CEDV), end-systolic coronary volume (CESV), maximum rate of increase in coronary pressure (C+dp/dtmax).…”
Section: Methodsmentioning
confidence: 99%